Sugarcane proteomics: An update on current status, challenges, and future prospects. Issue 10 (May 2015) - Barnabas, Leonard; Ramadass, Ashwin; Amalraj, Ramesh Sundar; Palaniyandi, Malathi; Rasappa, Viswanathan; Lüthje, Sabine; Deswal, Renu; Agrawal, Ganesh Kumar
<x xml:space="preserve">Abstract</x> Sugarcane is one of the most important commercial crops cultivated worldwide for the production of crystal sugar, ethanol, and other related by‐products. Unlike other comparable monocots like sorghum, maize, and rice, sugarcane genome by virtue of its polyploidy nature remains yet to be fully deciphered. Proteomics—an established complementary tool to genomics is at its infancy in sugarcane as compared to the other monocots. However, with the surge in genomics research accomplished by next‐generation sequencing platforms, sugarcane proteomics has gained momentum. This review summarizes the available literature from 1970 to 2014, which ensures a comprehensive coverage on sugarcane proteomics—a topic first of its kind to be reviewed. We herewith compiled substantial contributions in different areas of sugarcane proteomics, which include abiotic and biotic stresses, cell wall, organelle, and structural proteomics. The past decade has witnessed a paradigm shift in the pace with which sugarcane proteomics is progressing, as evident by the number of research publications. In addition to extensively reviewing the progress made thus far, we intend to highlight the scope in sugarcane proteomics, with an aspiration to instigate focused research on sugarcane to harness its full potential for the human welfare.